Do food skills protect from food insecurity? A study among asylum seekers living in Norway. (30th September 2020) - Terragni, L; Arnold, C; Henjum, S
Abstract: Background: Food insecurity has a high prevalence among asylum seekers living in Western countries. Previous studies suggest that food skills can protect against food insecurity. This study investigates the impact of food skills on food security and dietary diversity among refugees living in Norwegian reception centers. Methods: The study has a cross-sectional research design. Eight asylum reception centers where selected and 205 asylum seekers (131 men and 74 women) were recruited through convenience sampling among the largest asylum seeking groups. We measured food skills by adopting questions from the Canadian Community Health Survey 2013 Rapid Response on Food Skills. Food skills were divided into cooking skills (ability to prepare meals) and shopping skills (ability to plan meals and budgeting). Food security was measured with the 10-item version of the Radimer/Cornell Hunger and Food Insecurity Scale. Dietary data was collected via a 24-hour recall, and the Food and Agriculture Organization of the United Nations (FAO) dietary diversity score was calculated to assess dietary quality. Data were analyzed with bivariate logistic analysis. Results: Cooking skills and shopping skills contribute differently to food security and dietary diversity. Higher cooking skills were associated with higher dietary diversity but not with food security. Shopping skills were not associated with either food security or dietary diversity. Women had better cooking skills then men, but there were no gender differences in shopping skills. Married asylum seekers had better shopping skills than those who were not married. Conclusions: Cooking skills have an impact on dietary diversity, initiatives promoting cooking skills should be encouraged. Further research is needed on what kind of purchasing skills can be useful for asylum seekers coping. Despite high food skills the level of food insecurity remained high. Initiatives addressing the multiple causes of food insecurity are needed. Key messages: Food skills alone do not protect from food insecurity. Cooking skills are easier to transfer in a new food environment than shopping skills.